DETECTION, CORRECTION, AND FORECASTING OF HETEROSKEDASTICITY IN THE INDUSTRIAL SECTOR: THE CASE OF UZBEKISTAN (International Congress on Economics, Management and Business Studies, 2026)
This scientific article examines the relationship between investments in fixed capital and the gross value added of the industrial sector in the Republic of Uzbekistan using econometric methods. Based on quarterly statistical data for the period 2020–2025, a regression model was constructed. Heteroskedasticity was identified using the Breusch–Pagan and White tests and was subsequently corrected through a logarithmic transformation approach. In addition, forecast results for the period 2026–2030 are presented.
Keywords: Heteroskedasticity, regression analysis, Breusch–Pagan test, White test, logarithmic transformation, forecasting, industry, investments, Uzbekistan.